Monte Carlo design of a novel passive Regular Parallelepiped neutron spectrometer (TLD600/RPS); Radiation Physics and Chemistry; Vol. 236 - Vega-Carrillo H. R. Hector Rene; Baltazar-Raigosa A. Antonio; Hernandez-Davila V. M. Victor Martin; Gallego E. Eduard; Garcia-Fernandez G. F. Gonzalo; Bedenko S. V. Sergey Vladimirovich (2025, 2025)
Title screen